Highly improved passivation of PECVD p-type TOPCon by suppressing plasma-oxidation ion-bombardment-induced damages. (August 2022) - Ma, Dian; Liu, Wei; Xiao, Mingjing; Yang, Zhenhai; Liu, Zunke; Liao, Mingdun; Han, Qingling; Cheng, Hao; Xing, Haiyang; Ding, Zetao; Yan, Baojie; Wang, Yude; et al.
Highlights: Two-step oxidation (TSO) was effective in suppressing the ion-bombardment damage. PECVD p-TOPCon with TSO SiOx shows excellent passivation with an iV oc of ∼712 mV and a J 0, s of ∼10 fA/cm 2 . P-TOPCon with TSO SiOx produces a low contact resistivity of ∼10 mΩ·cm 2 . An efficiency of 24.6% based on the state-of-the-art technology is predicted by numerical simulations. Abstract: Tunnel oxide passivated contact (TOPCon) integrated with a plasma-enhanced chemical vapor deposition (PECVD) boron-doped polysilicon has the potential to achieve high-efficiency and low-cost solar cells. In this contribution, we explore the feasibility of using PECVD technology to prepare high-performance p-type TOPCon (p-TOPCon) by growing two-step oxidation (TSO), i.e., a nitric acid oxidation (NAOS) SiOx without ion-bombardment followed by a plasma-assist N2 O oxidation (PANO) SiOx layer. The experimental results reveal that for p-TOPCon structures on polished wafers with the conventional plasma oxidation SiOx, raising plasma oxidation powers to increase the thickness and oxidation degree of SiOx cannot ensure high-quality passivation due to the appearance of high-density defects caused by plasma ion-bombardment. In the presence of an additional NAOS SiOx layer, ion-bombardment-induced defects can be effectively suppressed, leading to a remarkable improvement in passivation properties. In detail, the optimal p-TOPCon with TSO SiOx achieves a maximum implied open-circuit voltage ( iV oc ) of ∼712 mV and a minimum single-sided saturation current density ( J 0, s ) of ∼10 fA/cm 2, manifesting an increment of iV oc by ∼10 mV, and a reduction of J 0, s by ∼5 fA/cm 2 . Finally, the numerical simulations reveal that n-type Si solar cells featuring p-TOPCon rear junction and Al electrode could receive an efficiency of 24.6% based on the state-of-the-art device fabrication technology. In general, this work provides a new way to boost the passivation quality of PECVD p-TOPCon devices.